Problem-Based Learning in Occupational Health & Safety: The Key to Fostering Critical Thinking and Creativity in Students - Ebrahimi, Mohammad Hossein; Gharibi, Vahid (Shahroud Journal of Medical Sciences, 2025)
Aims: This letter highlights the importance of Problem-Based Learning (PBL) in Occupational Health & Safety (OHS) education as a means to develop critical thinking and creativity among students.Methods: A narrative review of global PBL applications in OHS education and analysis of challenges in Iran’s educational system.Findings: Traditional teaching methods inadequately prepare students for complex OHS challenges. PBL promotes active learning, problem-solving, and creativity, as demonstrated by successful implementations in universities such as Maastricht and McMaster. Barriers in Iran include faculty unfamiliarity, rigid curricula, and assessment systems focused on memorization.Conclusion: Adoption of PBL, supported by faculty training, curriculum reform, modern technologies, and university-industry collaboration, is essential to cultivate competent OHS professionals in Iran.